Heavily Indebted Poor Countries (HIPC) Initiative and Multilateral Debt Relief Initiative (MDRI) : Status of Implementation 2008. (Policy Papers; Policy Paper ;, 2008)
This report provides an update on the status of implementation, impact and costs of the Enhanced Heavily Indebted Poor Country (HIPC) Initiative and the Multilateral Debt Relief Initiative (MDRI). With a view to the upcoming Financing for Development meetings in Doha, the report not only reports on recent progress since mid-2007, but also on developments since the Monterrey Consensus recommendations on external debt relief.